In Search of Meaning: A Preliminary Typology of Gay Male Spiritual Identity Development. Issue 1 (10th April 2019) - Hart, David; Brew, Leah; Pope, Mark
Abstract : Reconciliation of the conflict between religious identity and sexual orientation has been related to a number of psychological challenges (Lease, Horne, & Noffsinger‐Frazier, 2005; Schuck & Liddle, 2001), and little is known about the convergence of spiritual identity, distinctly defined as separate from religious identity, and sexual orientation identity. This qualitative inquiry investigated the process by which 7 Caucasian gay men from a variety of religious backgrounds constructed spiritual identities outside the realm of institutionalized religion. From the findings, the authors hypothesize a typology of spiritual development influenced by religions of origin. Limitations of the study, implications, and future directions in research are also addressed.